Measurement of PM2.5 Concentration at the Photocopy Machine Center at Brawijaya University Environment - Arinto Y. P. Wardoyo; Unggul P Juswono; Rowinda Sitanggang (Natural B, Journal of Health and Environmental Sciences, 2012)
Air pollution is one of matters that faced by all states in this world. In outline air pollution can be distinguished into two there are outdoor pollutant and indoor pollutant. Material or substance which can pollute the air could organized as gas and particle. One source of indoor pollutant is photocopy machine. This study presents the measurements of PM2,5 concentration at several copy centers in Brawijaya University. The aims were to measure the PM2,5 concentrations at the eight copy centers using the Kanomax Mass Monitor Piezobalance 3522. The results from nine hours average PM2,5 value as that during business ranged from 0,02-0,09 mg/m3. The showed that the six of the 8 copy centers having the PM2,5 concentration more than the Indonesia governments air quality standard of 0,035 mg/m3 at 24 hours.